Relationship between Structural Characteristics of Cellulose Nanocrystals Obtained from Kraft Pulp - María Graciela Aguayo; Arturo Fernández-Pérez; Claudia Oviedo; Guillermo Reyes; Pablo Reyes-Contreras (Nanomaterials, 2020)
Kraft pulp cellulose was hydrolyzed using sulfuric acid, under different thermophysical conditions of temperature, time, pulp concentration, and sonication time. The experimental design revealed the effect of these conditions and their interaction on the hydrolysis yield obtained. In addition, the top five cellulose nanocrystals (CNCs) yields from this experiment design were analyzed. The results obtained indicated that CNCs possess a morphology that can be described as individualized rod particles, with average diameters less than 50 nm and different size distribution. In the analysis of CNCs features, significant Pearson correlations were established between the crystallinity of the CNC, CNC yield, and interplanar crystallites distance (Δd/d). The thermogravimetric (DTG) profiles exhibited two CNCs degradation stages, where the second stage CNCs degradation showed a significative correlation with CNC sulfur content. In our analysis, the crystallographic parameters exhibited a correlation with the mechanical behavior of the CNC, since the potential variation between the distances of the crystalline planes is related to the stress and deformation present in the crystallites of CNCs. This study provides new knowledge regarding CNCs, further enhancing information for CNC-based industries and the processability of CNCs for the development of new materials.